Thermal interface material based on elastomer glass and preparation method thereof
By achieving the highly vertical orientation of the thermal filler in a highly flexible vitreous matrix, the hardness and consistency problems of existing high thermal conductivity composite materials are solved, and the effect of combining high thermal conductivity and flexibility is achieved.
Patent Information
- Application Number
- CN202411869280.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-12-18
AI Technical Summary
While the existing high-thermal conductivity composite materials improve thermal conductivity, they increase hardness and reduce stereo consistency, and the low content of thermal conductivity fillers limits the vertical thermal conductivity coefficient.
Highly flexible vitreous matrix is prepared by using diglycidyl ether-terminated liquid polysulfide prepolymers with a large number of disulfide dynamic bonds, and the highly vertical orientation of the thermally conductive filler is achieved through hot pressing and stacking welding processes to form a vertically arranged composite material.
The combination of high flexibility and high thermal conductivity is achieved, with a vertical thermal conductivity of 25.0W·m-1K-1, and has spontaneous interface contact behavior and low interface thermal resistance.
Smart Images

Figure CN119912790A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of organic and inorganic composite materials, and in particular to a thermal interface material based on elastomer-like glass and a preparation method thereof. Background Art
[0002] With the surge in power and heat generation of electronic devices, heat dissipation has become a bottleneck hindering the development of advanced electronic devices. It is worth noting that when heat passes through the macroscopic interface between the heat source and the heat sink, the air grooves generated by the incomplete interface contact will seriously hinder the heat transfer. Using thermal interface materials (TIM) to enhance interfacial heat transfer is the most common engineering strategy, and the development of high-performance TIM has become a common goal of practitioners around the world.
[0003] However, high thermal conductivity composite materials usually require a large amount of thermal conductive fillers to build a complete heat transfer path, which increases the hardness of the composite material and seriously weakens the three-dimensional consistency. And the most common thermal conductive pad is the thermal conductive silicone pad. In order to have good flexibility, the cross-linking density of the silicone matrix is usually reduced, which will cause incomplete curing and a certain amount of oil leakage. Even if the high-filled TIM has a high κ ⊥ , its thermal conductivity will also be affected by the high interface thermal resistance (R c ) is affected. Obviously, there are more reports on flexible TIMs with low thermal resistance. Some researchers have tried to construct a continuous filler network at low filling by specific methods, such as ice template method, polymer template method and foam template method. Zhao et al. prepared a new polymer composite composed of foam graphene (GF), carbon black (CB) and polydimethylsiloxane (PDMS) by foam template method. When the filler content reached 8wt%, GF and CB formed an effective heat transport double network inside the composite material, and the thermal conductivity of 8wt% CB / GF / PDMS composite material reached 0.686W m -1 K -1 Although these methods improve the thermal conductivity of fillers, the low content of thermally conductive fillers limits the κ ⊥ . Summary of the invention
[0004] In view of the problems existing in the above-mentioned prior art, an object of the present invention is to provide a thermal interface material based on elastomer-like glass and a preparation method thereof.
[0005] The present invention prepares a highly flexible glass-like matrix based on a diglycidyl ether-terminated liquid polysulfide prepolymer (EPS) with a large number of disulfide dynamic bonds. At the same time, a highly vertical orientation of the thermally conductive filler is achieved through a process combining hot pressing and stacking welding, thereby achieving effective through-plane heat conduction. Due to the bond exchange reaction of a large number of active disulfide bonds in the matrix, the customized glass matrix has good self-healing properties, especially its hot-pressed film after filling with graphite shows excellent weldability, which is the basis for the feasibility of the vertical orientation process. When the thermally conductive filler is 80 parts, the κ of the prepared vertically arranged composite material (VAGC) is ⊥ Up to 25.0W·m -1 K -1 More importantly, a unique spontaneous interfacial contact behavior is found on this glass-like composite, driven by the time-temperature dependent unstable dynamics and the thermodynamically high surface free energy. c Much lower than commercial TIMs using traditional silicon substrates.
[0006] One of the purposes of the present invention is to provide a thermal interface material based on elastomeric glass, which is prepared from raw materials including diglycidyl ether-terminated liquid polysulfide prepolymer, methyltetrahydrophthalic anhydride, ethylene glycol diglycidyl ether, a catalyst and a thermal conductive filler.
[0007] In the thermal interface material, based on 100 parts by weight of diglycidyl ether-terminated liquid polysulfide prepolymer, 20 to 50 parts by weight of methyltetrahydrophthalic anhydride, 2 to 20 parts by weight of ethylene glycol diglycidyl ether, 0.5 to 2 parts by weight of catalyst, and 20 to 100 parts by weight of thermal conductive filler.
[0008] Preferably, based on 100 parts by weight of the diglycidyl ether-terminated liquid polysulfide prepolymer, 30 to 40 parts by weight of methyltetrahydrophthalic anhydride, 10 to 15 parts by weight of ethylene glycol diglycidyl ether, 1 to 1.5 parts by weight of the catalyst, and 60 to 80 parts by weight of the thermal conductive filler.
[0009] Specifically, based on 100 parts by weight of the diglycidyl ether-terminated liquid polysulfide prepolymer, the amount of methyltetrahydrophthalic anhydride can be 20, 25, 30, 35, 40, 45, 50 parts by weight, etc.
[0010] Specifically, based on 100 parts by weight of the diglycidyl ether-terminated liquid polysulfide prepolymer, the amount of ethylene glycol diglycidyl ether can be 2, 5, 10, 15, 20 parts by weight, etc.
[0011] Specifically, based on 100 parts by weight of the diglycidyl ether-terminated liquid polysulfide prepolymer, the amount of the catalyst can be 0.5, 1, 1.5, 2 parts by weight, etc.
[0012] Specifically, based on 100 parts by weight of the diglycidyl ether-terminated liquid polysulfide prepolymer, the thermal conductive filler can be 20, 30, 40, 50, 60, 70, 80, 90, 100 parts by weight, etc.
[0013] The thermal conductive filler is selected from at least one of graphite, whisker carbon nanotubes and carbon fibers.
[0014] The particle size of the thermal conductive filler is 50nm-600μm.
[0015] The catalyst is 2,4,6-tris(dimethylaminomethyl)phenol.
[0016] The thermally conductive fillers are arranged in order in any direction relative to the thickness of the thermal interface material.
[0017] Various additives commonly used in the art may also be added to the thermal interface material as required.
[0018] In the present invention, under the action of a catalyst, methyltetrahydrophthalic anhydride can promote the ring opening and cross-linking of epoxy groups in a diglycidyl ether-terminated liquid polysulfide prepolymer. In order to improve the toughness and elasticity of the epoxy cross-linked product, ethylene glycol diglycidyl ether is added to increase the content and reaction activity of the epoxy groups in the reactants.
[0019] The second object of the present invention is to provide a method for preparing the thermal interface material, comprising hot pressing and stacking welding raw materials including diglycidyl ether-terminated liquid polysulfide prepolymer, methyltetrahydrophthalic anhydride, ethylene glycol diglycidyl ether, a catalyst and a thermally conductive filler.
[0020] Preferably, the preparation method comprises the following steps:
[0021] (1) mixing raw materials including a diglycidyl ether-terminated liquid polysulfide prepolymer, methyltetrahydrophthalic anhydride, ethylene glycol diglycidyl ether, a catalyst and a thermal conductive filler to obtain a premix;
[0022] (2) subjecting the premix to high temperature hot pressing to prepare a composite film;
[0023] (3) stacking and welding the composite film to obtain a composite block;
[0024] (4) Cutting the composite material block.
[0025] In the step (2):
[0026] The temperature of high temperature hot pressing is 100-170°C, for example, 100°C, 120°C, 150°C, 170°C, etc.;
[0027] The time of high temperature hot pressing is 0.5 to 2 hours;
[0028] The thickness of the composite material film is 0.08 to 2 mm, for example, 0.08 mm, 0.1 mm, 0.5 mm, 1 mm, 1.5 mm, 2 mm, etc.
[0029] In the step (3):
[0030] The welding temperature is 100-150°C, for example, 100°C, 120°C, 150°C, etc.;
[0031] The thickness of the composite material block is ≥4cm.
[0032] The key to the novel TIM in the present invention is to use a diglycidyl ether-terminated liquid polysulfide prepolymer (EPS) as a base material, and stir it evenly with methyltetrahydrophthalic anhydride and ethylene glycol diglycidyl ether (EDGE) and 2,4,6-tris(dimethylaminomethyl)phenol as a catalyst to obtain an EPS mixture; the mixture is heated and cured at 100-170°C in a vacuum drying oven at normal pressure for 0.5-2h to obtain a highly flexible EPS-like glass matrix.
[0033] Beneficial effects of the present invention:
[0034] (1) The EPS prepared in the present invention is used as a substrate of TIM and has good flexibility. The EPS substrate has excellent self-healing properties and good adhesion.
[0035] (2) The present invention orients the thermal interface material by hot pressing, and through the "stacking-welding method" and changing the orientation direction of the thermally conductive filler, a glass-like TIM with vertically arranged thermally conductive fillers can be prepared, which has an extremely high thermal conductivity in the vertical direction.
[0036] (3) Different from the physical flexibility of traditional thermal pads, the glass-like thermal interface material of the present invention has spontaneous contact behavior on the substrate surface under the joint drive of stress relaxation and high surface free energy. Therefore, this glass-based TIM exhibits low R under extremely low additional pressure (1 psi). c。 BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 (a) is a typical stress-strain curve of EPS glass with different cross-linking degrees in Examples 3, 4, and 5; Figure 1 (b) is the Young's modulus of EPS glass bodies with different crosslinking degrees in Examples 3, 4, and 5.
[0038] Figure 2 (a) is an optical microscope image of the self-healing phenomenon of EV-1 of Example 3 at 60°C; Figure 2(b) is a typical stress-strain curve of the original EPS vitreous and the healed samples of Examples 3, 4, and 5; Figure 2 (c) is the healing efficiency of the EPS-type vitreous bodies of Examples 3, 4, and 5.
[0039] Figure 3 (a) is the bonding shear strength between EV-1 of Example 3 and different substrates; Figure 3 (b) is a photo of the overlap shear test between EV-1 of Example 3 and different substrates.
[0040] Figure 4 (a) is the kappa of VAGC of Examples 1, 2, and 4 with graphite of different sizes ⊥ and κ ∥ Its κ ⊥ / κ ∥ ; Figure 4 (b) κ of 600 μm graphite composites with different filler distributions ⊥ .
[0041] Figure 5 The κ of the VAGC of Example 4 and the material reported in the previous literature ⊥ contrast.
[0042] Figure 6 (a) is the R of the TIM of Example 4 at 1 psi pressure c ; Figure 6 (b) is the R of TIM at 1 psi pressure t . DETAILED DESCRIPTION
[0043] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.
[0044] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0045] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation method disclosed in the prior art.
[0046] According to a preferred embodiment of the present invention, the method for preparing the thermal interface material comprises the following steps:
[0047] ① The EPS matrix, methyltetrahydrophthalic anhydride, ethylene glycol diglycidyl ether, 2,4,6-tris(dimethylaminomethyl)phenol catalyst and thermal conductive filler are uniformly mixed by a common polymer mixing method to obtain a TIM premix; ② The premix is subjected to high temperature hot pressing at 100-170°C to prepare a parallel-arranged graphite composite material with a thickness of 0.08-2mm; ③ After the graphite composite film is stacked to a certain thickness (≥4cm), two steel plates with positioning holes on the upper and lower sides are used to press the stacked film and fix it with bolts. The fixed stacked film is welded in a drying oven at a welding temperature of 100-150°C for 0.5-2h to obtain a complete composite block; ④ The block material is longitudinally cut in a specific direction to obtain a vertically oriented TIM (VAGC), wherein the thickness of the TIM can be adjusted according to actual conditions.
[0048] The formula is 100 parts of EPS matrix, 20-50 parts of methyltetrahydrophthalic anhydride, 2-20 parts of ethylene glycol diglycidyl ether, 0.5-2 parts of 2,4,6-tris(dimethylaminomethyl)phenol, and 20-100 parts of one or more of graphite (75-600μm), carbon fiber (200μm), whisker carbon nanotube (75nm) and the like of different particle sizes.
[0049] The thickness of the TIM in the following examples is 2 mm.
[0050] Example 1
[0051] 100 parts of EPS rubber, 40 parts of methyltetrahydrophthalic anhydride, 2 parts of EDGE, 0.5 parts of 2,4,6-tris(dimethylaminomethyl)phenol, and 50 parts of graphite with a particle size of 75μm were mixed evenly in a non-invasive material homogenizer. Then it was hot-pressed at 100°C for 2h to obtain a 0.1mm thick film. The films were stacked and welded at 120°C to form a complete block. The block material was cut into TIMs of the required thickness, and the cutting direction was perpendicular to the orientation direction of the two-dimensional filler. The thermal conductivity of the prepared TIM in the vertical direction is 16.9W / mK.
[0052] Example 2
[0053] 100 parts of EPS rubber, 40 parts of methyltetrahydrophthalic anhydride, 5 parts of EDGE, 0.5 parts of 2,4,6-tris(dimethylaminomethyl)phenol, and 50 parts of graphite with a particle size of 200μm were mixed evenly in a non-invasive material homogenizer. Then it was hot pressed at 140°C for 0.5h to obtain a 0.1mm thick film. The films were stacked and welded at 120°C to form a complete block. The block material was cut into TIMs of the required thickness, and the cutting direction was perpendicular to the orientation direction of the two-dimensional filler. The thermal conductivity of the prepared TIM in the vertical direction is 17.8W / mK.
[0054] Example 3
[0055] 100 parts of EPS rubber, 40 parts of methyltetrahydrophthalic anhydride, 5 parts of EDGE, 1 part of 2,4,6-tris(dimethylaminomethyl)phenol, and 50 parts of graphite with a particle size of 600μm were mixed evenly in a non-invasive material homogenizer. Then it was hot pressed at 100°C for 1h to obtain a 0.1mm thick film. The films were stacked and welded at 120°C to form a complete block. The block material was cut into TIMs of the required thickness, and the cutting direction was perpendicular to the orientation direction of the two-dimensional filler. The thermal conductivity of the prepared TIM in the vertical direction is 21W / mK.
[0056] 100 parts of EPS rubber, 40 parts of methyltetrahydrophthalic anhydride, 5 parts of EDGE, and 1 part of 2,4,6-tris(dimethylaminomethyl)phenol were mixed and kneaded in a non-invasive material homogenizer, and then hot-pressed at 100° C. for 1 hour to obtain an EPS-like glass (EV-1).
[0057] Example 4
[0058] 100 parts of EPS rubber, 40 parts of methyltetrahydrophthalic anhydride, 10 parts of EDGE, 1 part of 2,4,6-tris(dimethylaminomethyl)phenol, and 50 parts of graphite with a particle size of 600μm were mixed evenly in a non-invasive material homogenizer. Then it was hot pressed at 100°C for 1h to obtain a 0.1mm thick film. The films were stacked and welded at 120°C to form a complete block. The block material was cut into TIMs of the required thickness, and the cutting direction was perpendicular to the orientation direction of the two-dimensional filler to obtain VAGC. The thermal conductivity of the prepared TIM in the vertical direction is 25W / mK.
[0059] 100 parts of EPS rubber, 40 parts of methyltetrahydrophthalic anhydride, 10 parts of EDGE, and 1 part of 2,4,6-tris(dimethylaminomethyl)phenol were mixed and kneaded in a non-invasive material homogenizer, and then hot-pressed at 100° C. for 1 hour to obtain EPS glass (EV-2).
[0060] Example 5
[0061] 100 parts of EPS rubber, 40 parts of methyltetrahydrophthalic anhydride, 15 parts of EDGE, 1 part of 2,4,6-tris(dimethylaminomethyl)phenol, and 50 parts of graphite with a particle size of 600μm were mixed evenly in a non-invasive material homogenizer. Then it was hot-pressed at 100°C for 1h to obtain a 0.1mm thick film. The films were stacked and welded at 120°C to form a complete block. The block material was cut into TIMs of the required thickness, and the cutting direction was perpendicular to the orientation direction of the two-dimensional filler. The thermal conductivity of the prepared TIM in the vertical direction is 20W / mK.
[0062] 100 parts of EPS rubber, 40 parts of methyltetrahydrophthalic anhydride, 15 parts of EDGE, and 1 part of 2,4,6-tris(dimethylaminomethyl)phenol were mixed and kneaded in a non-invasive material homogenizer, and then hot-pressed at 100° C. for 1 hour to obtain EPS-like glass (EV-3).
[0063] Example 6
[0064] 100 parts of EPS rubber, 40 parts of methyltetrahydrophthalic anhydride, 10 parts of EDGE, 1 part of 2,4,6-tris(dimethylaminomethyl)phenol, and 30 parts of graphite with a particle size of 600μm. Mix them evenly in a non-invasive material homogenizer. Then hot press them at 120°C for 1h to obtain a 0.1mm thick film. Stack the films and weld them at 120°C to form a complete block. Cut the block material into TIM of the required thickness, and the cutting direction is perpendicular to the orientation direction of the two-dimensional filler. The thermal conductivity of the prepared TIM in the vertical direction is 15W / mK.
[0065] Example 7
[0066] 100 parts of EPS rubber, 40 parts of methyltetrahydrophthalic anhydride, 15 parts of EDGE, 2 parts of 2,4,6-tris(dimethylaminomethyl)phenol, and 40 parts of graphite with a particle size of 600μm. Mix them evenly in a non-invasive material homogenizer. Then hot press them at 130°C for 0.5h to obtain a 0.1mm thick film. Stack the films and weld them at 120°C to form a complete block. Cut the block material into TIM of the required thickness, and the cutting direction is perpendicular to the orientation direction of the two-dimensional filler. The thermal conductivity of the prepared TIM in the vertical direction is 19W / mK.
[0067] Comparative Example 1
[0068] Laird Technologies' Tflex 740 was used, with a thermal conductivity of 5 W / mK in the vertical direction.
[0069] Comparative Example 2
[0070] 100 parts of EPS rubber, 40 parts of methyltetrahydrophthalic anhydride, 10 parts of EDGE, 1 part of 2,4,6-tris(dimethylaminomethyl)phenol, and 50 parts of graphite with a particle size of 600μm were mixed evenly in a non-invasive material homogenizer. Then, it was hot-pressed at 120℃ for 1h to obtain a 2mm film, which is a randomly distributed graphite composite material (RAGC). The thermal conductivity of the prepared TIM in the vertical direction is 11.1W / mK.
[0071] According to the accompanying drawings of the present invention, it can be seen that:
[0072] (1) The present invention prepares an EPS as a substrate for TIM, which has good flexibility and increases with the decrease of EDGE dosage ( Figure 1 ). EV-1, EV-2, and EV-3 correspond to Examples 3, 4, and 5, respectively. Figure 2 In (a), the self-healing phenomenon caused by the dynamic network of the EPS matrix can be observed at 60°C. The scratches on the sample completely disappeared after 60 minutes, indicating that the EPS matrix has excellent self-healing properties. Figure 2 (b) is the stress-strain curve of the original sample and the healed sample, and the ratio of the tensile strength between the two is calculated. Figure 2 (c) It can be seen that EV-1 has the highest tensile strength recovery rate, reaching 99.9%. Figure 3 Lap shear tests were carried out for the EPS matrix on substrates of different materials, and the adhesion of the EPS matrix was evaluated by its shear strength. It was found that the EPS matrix had good adhesion.
[0073] (2) The composite material was oriented by hot pressing, and the graphite was vertically arranged by "stacking-welding" and changing the orientation direction of graphite to prepare a glass-like TIM with extremely high thermal conductivity in the vertical direction. Among all the reported graphite composites, VAGC has a very outstanding k⊥, especially since it is filled with less filler and the EPS matrix itself has a lower thermal conductivity (0.12 W·m -1 ·K -1 ).
[0074] The thermal conductivity of graphite is anisotropic, and its κ ⊥ (perpendicular thermal conductivity) is different from the excellent κ ∥ (parallel thermal conductivity), its κ⊥ is only 2.0 W·m -1 ·K -1This also leads to significant anisotropy in the thermal conductivity of VAGC (Example 4). Compared with RAGC (Comparative Example 2) and PAGC (0.1 mm thick films obtained in Example 4 are directly stacked into 2 mm), VAGC has a k⊥ of 25.0 W·m -1 ·K -1 , much higher than RAGC and PAGC. ( Figure 4 b)
[0075] (3) Different from the physical flexibility of traditional thermal pads, the glass-like composite material has spontaneous contact behavior on the substrate surface driven by stress relaxation and high surface free energy. EPS glass-like TIM also has a temperature-dependent R under a low pressure of 1 psi. c ( Figure 6 As the temperature rises from 30°C to 85°C, the R c Only 131.4mm 2 ·W.K. -1 and 165.9mm 2 ·W.K. -1 , a decrease of more than 40%. The Rc of the commercially available silicone rubber TIM (model Tflex740) is stable at 880.0mm in this temperature range. 2 ·W.K. -1 Compared with Tflex 740, EPS-type glass TIM has an R c A drop of more than 81.1%.
Claims
1. A thermal interface material based on elastomeric glass is prepared from raw materials including diglycidyl ether-terminated liquid polysulfide prepolymer, methyltetrahydrophthalic anhydride, ethylene glycol diglycidyl ether, a catalyst and a thermal conductive filler.
2. The thermal interface material according to claim 1, characterized in that: Based on 100 parts by weight of diglycidyl ether-terminated liquid polysulfide prepolymer, 20 to 50 parts by weight of methyltetrahydrophthalic anhydride, 2 to 20 parts by weight of ethylene glycol diglycidyl ether, 0.5 to 2 parts by weight of catalyst and 20 to 100 parts by weight of thermal conductive filler are used.
3. The thermal interface material according to claim 2, characterized in that: Based on 100 parts by weight of diglycidyl ether-terminated liquid polysulfide prepolymer, 30-40 parts by weight of methyltetrahydrophthalic anhydride, 10-15 parts by weight of ethylene glycol diglycidyl ether, 1-1.5 parts by weight of catalyst and 60-80 parts by weight of thermal conductive filler are used.
4. The thermal interface material according to claim 1, characterized in that: The thermally conductive filler is selected from at least one of graphite, whisker carbon nanotubes, and carbon fibers; and / or, The particle size of the thermal conductive filler is 50nm-600μm.
5. The thermal interface material according to claim 1, characterized in that: The catalyst is 2,4,6-tris(dimethylaminomethyl)phenol.
6. The thermal interface material according to claim 1, characterized in that: The thermally conductive fillers are arranged in order in any direction relative to the thickness of the thermal interface material.
7. A method for preparing a thermal interface material according to any one of claims 1 to 6, comprising hot pressing and stacking welding raw materials including a diglycidyl ether-terminated liquid polysulfide prepolymer, methyltetrahydrophthalic anhydride, ethylene glycol diglycidyl ether, a catalyst and a thermally conductive filler.
8. The preparation method according to claim 7, characterized in that The following steps are involved: (1) mixing raw materials including a diglycidyl ether-terminated liquid polysulfide prepolymer, methyltetrahydrophthalic anhydride, ethylene glycol diglycidyl ether, a catalyst and a thermal conductive filler to obtain a premix; (2) subjecting the premix to high temperature hot pressing to prepare a composite film; (3) stacking and welding the composite film to obtain a composite block; (4) Cutting the composite material block.
9. The preparation method according to claim 8, characterized in that In step (2): the temperature of high temperature hot pressing is 100 to 170° C.; and / or, The high temperature hot pressing time is 0.5 to 2 hours; and / or, The thickness of the composite film is 0.08 to 2 mm.
10. The preparation method according to claim 8, characterized in that In step (3): the welding temperature is 100 to 150° C.; and / or, The thickness of the composite material block is ≥4cm.
Citation Information
Patent Citations
Electric-insulating heat-conducting polyphenyl thioether composite material and preparation method thereof
CN102532897A
Lightweight flexible thermal interface material and preparation method thereof
CN108456343A
Gel-type thermal interface material with low pre-curing viscosity and elastic properties post-curing
CN113840881A
Glass-filled composition based on polyphenylenesulphide
RU2635136C1
Thermal interface materials
TW202110961A
Cited By
Ultra-high molecular weight polyvinyl lubricating composite material and preparation method thereof
CN122127685A
An ultra-high molecular weight polyethylene-based lubricious composite material and a method of making the same
CN122127685B